Rooftop Rain Water Harvesting Technology and Women Time Allocation in District Bagh and Battagram Pakistan. (The Pakistan Development Review, 2011)
Water is essential requirement of life and its accessibility is the basic right of all human beings. Safe drinking water is an essential component of primary health. It plays a vital role in livelihood, food security and sustainable development. Rooftop Rainwater Harvesting Technology (RRWH) is a best alternative approach to conserve and supply water. Especially, it is crucial in seismically sensitive, geographically uneven, and countryside areas. A large majority of population in Pakistan is living in areas, where access to safe drinking water is very serious issue. In these areas most vulnerable segment of population is women because they are the ones who have to fetch water from far flung areas for their daily consumption. In order to resolve the issue of water in Pakistan, a number of public and private agencies are working in this field. Different approaches, techniques, and practices are being adopted to address this issue. Present study evaluates the impact of RRWH technology with special reference to women time allocation in Bagh and Battagram districts of Pakistan. Analyses were carried out using Ordinary Least Square (OLS) technique to quantify the results. The results reveal that RRWH technology is viable, time saving, women friendly, and sustainable source of safe drinking water supply, especially in seismically sensitive, geographically uneven, and countryside areas of Pakistan. JEL classification: O13, Q25, Q56, Q58, R28 Keywords: Rooftop Rain Water Harvesting: Safe Drinking Water, Seismically Sensitive, Geographically Uneven, and Countryside: Women, AJK and KP, Pakistan.